Research on user experience optimization strategy of e-commerce platform with biomechanics principle—Analysis based on data mining - Zheng, Meng (Molecular & Cellular Biomechanics, 2025)
This study discusses the strategy of combining biomechanics principle and data mining technology to optimize the user experience of e-commerce platform. Through biomechanical principles, the interface design and interaction mode are optimized, and the operation comfort and efficiency are improved. Data mining technology deeply analyzes user behavior data, reveals user needs and pain points, and provides decision support for personalized service and interface design. The study proposes specific optimization strategies, such as personalized recommendation, interaction process simplification, response speed improvement and equipment adaptation, and emphasizes the importance of user feedback and continuous optimization mechanism. These strategies effectively improve the user experience and enhance the user stickiness and market competitiveness of the platform.